The jazz standards a guide to the repertoire - Gioia, Ted (Oxford University Press, 2012)
This comprehensive guide tells the story of more than 250 key jazz songs and includes a listening guide to more than 2,000 recordings. The author draws on his deep personal experience with jazz music to outline the history and significance of the compositions and tell how they have been performed by different generations of jazz artists.